Profil Faktor Risiko Stroke Tenaga Keperawatan RSI Fatimah Cilacap - Nancy Susanita; Ratna Indriawati (Jurnal Keperawatan Muhammadiyah, 2021)
Research objective: The research objective is to examine and provide information about the risk factors for stroke in nursing staff. Research method: The study was conducted on 147 nursing staff, the research design was quantitative observational with a cross sectional approach using a Stroke Risk Scorecard questionnaire. The analysis of the results was carried out using a description method that produced a percentage.   Results: The results obtained are the risk of stroke by nursing staff at RSI Fatimah in a low level of 63.9%, a warning of 21.8% and a high risk of 14.3%. Nursing staff with a high risk of stroke are in the age range of 26-35 years. Conclusion: The conclusion of the study is that most of the nursing staff at RSI Fatimah Cilacap are at low risk and can control stroke well.